Bahasa Indonesia as Official National Language: The Legal Aspect of Presidential Regulation Number 63 of 2019 - Utama, Muhamad Adji Rahardian (Law Research Review Quarterly, 2020)
Indonesia as an independent and sovereign country that has now reached the age of 74th of the independence itself. As an independent and sovereign country, Indonesia has the official language of its own country, the Bahasa Indonesia that has been recognized by the world. The use of Bahasa Indonesia is also important in its use and application in the life of national and state of the day in Indonesian society itself as stipulated by the Law of the Republic of Indonesia Number 24 Year 2009 about the flags, languages, and emblems of the state, and national anthem. Pursuant to Chapter 1 of Article 1 of Paragraph 2 of the Law of the Republic of Indonesia number 24 year 2009 states that the unitary State language of the Republic of Indonesia hereinafter referred to as Bahasa Indonesia is the official national language used in all Unitary State territory of the Republic of Indonesia. So it can be said that Bahasa Indonesia is a vital thing in this Republic of Indonesia unitary state